The Roman Inquisition : center versus peripheries - Aron-Beller, Katherine; Black, Christopher F., 1941- (Catholic Christendom, 1300-1700., 2018)
In 'The Roman Inquisition: Centre versus Peripheries', two inquisitorial scholars, Black who has published on the institutional history of the Italian Inquisitions and Aron-Beller whose area of expertise are trials against Jews before the peripheral Modenese inquisition, jointly edit an essay collection that studies the relationship between the Sacred Congregation in Rome and its peripheral inquisitorial tribunals. The book analyses inquisitorial collaborations in Rome, correspondence between the Centre and its peripheries, as well as the actions of these sub-central tribunals. It discusses the extent to which the controlling tendencies of the Centre filtered down and affected the peripheries, and how the tribunals were in fact prevented by local political considerations from achieving the homogenizing effect desired by Rome.